CONTROL SYSTEM DESIGN AND SCREEN CV. CEREMAI AGUNG RAYA - Risandi Aldino; Ire Puspa Wardhani, SKom, MMSi (Jurnal Sistem Informasi, 1998)
With the current system will be able to assist the presentation of the report or information is needed to correct and appropriate. With the acquired information is true and accurate, can help manage the company so as not to late to take steps necessary to ensure smooth company. With the inventory control system can assist enterprise to quickly mengetauhi circumstances existing goods in persediaanya, sold goods, new goods received and forth. and can prevent the accumulation of excess inventory in the warehouse or shortage of goods in warehouse inventories.